Enhancing the Engagement of Third-Grade Students in Pancasila Education Through the “Make a Match” Cooperative Learning Model - Dika Binti Johari; Zahwa Sahara; Rizky Tidarwati Pratiwi; Nur Imamah; Hana Rosyida; Intan Kusumawati (Yayasan Citra Dharma Cindekia, 2026)
This study aims to increase third-grade students' engagement in Pancasila Education at SDN Pernajuh through the “Make a Match” cooperative learning model. A Classroom Action Research (CAR) method based on the Kemmis and McTaggart model was conducted across two cycles (planning, implementation, observation, reflection). Subjects were 19 third-grade students during the second semester of the 2025/2026 academic year. Data were collected via observation, interviews, tests, and documentation, then analyzed using descriptive quantitative and qualitative methods. Results showed the Make a Match model significantly increased student participation from 42% (less active) in the pre-cycle to 68% (moderately active) in Cycle I, reaching 87% (highly active) in Cycle II. This improvement was evident in students’ confidence, collaborative skills, enthusiasm during card matching, and task punctuality. In conclusion, the Make a Match cooperative model effectively enhances third-grade students' learning engagement in Pancasila Education.